Covert Sensitization Treatment with Alcoholics - Fleiger, D. L.; Zingle, H. W. (Canadian Journal of Counselling and Psychotherapy, 2012)
An attempt was made to determine whether a behaviorally oriented conditioning approach, "covert sensitization," is more effective in the treatment of alcoholism than the commonly used problem-solving approach; and whether female counselors employing covert sensitization are more successful than males.A sample of 32 subjects selected on admission to Henwood Rehabilitation Centre, an in-patient facility of the Division of Alcoholism, in the Province of Alberta, was assigned to 2 treatment groups for the purpose of statistical comparison and evaluation.Eight staff counselors (4 males, 4 females) especially prepared in a 2-week, in-service workshop conduced covert sensitization with patients in treatment group 1 ; they also participated at least 50 percent of the time with other staff counselors in the problem-solving approach utilized in treatment group 2.A 3-month period of abstinence following discharge from Henwood was selected as the criterion measure in determining the results of treatment outcome. Appropriate statistical analysis of the criterion data yielded support for both the hypotheses tested.